Family Dynamics over the Life Course Foundations, Turning Points and Outcomes - Baxter, Janeen; Lam, Jack.; Povey, Jenny; Lee, Rennie; Zubrick, Stephen R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book examines how families and other social institutions interact to shape outcomes over the life course. It considers how to use research evidence to reduce social disadvantage through translation of evidence to support public policies and programs. The chapters focus on key life course stages such as early child development, adolescence, emerging adulthood, parenting, marriage, relationships and ageing, as well as examining experiences and outcomes for selected social groups such as Indigenous children, migrants and refugees, and gay, lesbian and bisexual groups. The book presents evidence using high-quality and recent data. With a focus on Australia, the volume provides new insights into how context shapes life course pathways and outcomes and a contrast to work that typically focuses on Europe and the United States. It will be of value to anyone interested in understanding how family background and life course pathways influence social disadvantage.
Chapter 1. Introduction -- Chapter 2. Families, Life Courses and the Intergenerational Transmission of Social Disadvantage in Australia -- Chapter 3. Early Years and Disadvantage: Matching Developmental Circumstances in Populations to Prevention and Intervention Opportunities -- Chapter 4. Cultural Identity and Social and Emotional Wellbeing in Aboriginal and Torres Strait Islander Children -- Chapter 5. Refugee Children in Australia: Well-being and Integration -- Chapter 6. Adolescence a Period of Vulnerability and Risk for Adverse Outcomes across the Life Course: The Role of Parent Engagement in Learning -- Chapter 7. Differences in Higher Education Access, Participation and Outcomes by Socioeconomic Background: A Life Course Perspective -- Chapter 8. Emerging Adulthood in Australia: How is this Stage Lived? -- Chapter 9. Labour Market Participation: Family and Work Challenges across the Life Course -- Chapter 10. Marriage Matters. Or Does it? -- Chapter 11. Parenthood: Disrupting the Intergenerational Transmission of Social Disadvantage -- Chapter 12. Intergenerational Processes of Disadvantage in the Lives of Lesbian, Gay and Bisexual Australians: From Relationships with Parents to Parenting Expectations -- Chapter 13. Ageing and Loneliness: A Life Course and Cumulative Disadvantage Approach -- Chapter 14. Influencing Social Policy on Families Through Research in Australia -- Chapter 15 Emerging Directions and New Challenges.
Keywords: Life cycle, Human; Sociology; Social groups; Life Course; Sociology of Family, Youth and Aging